Karnofsky Performance Status as A Predictive Factor for Cancer-Related Fatigue Treatment with Astragalus Polysaccharides (PG2) Injection—A Double Blind, Multi-Center, Randomized Phase IV Study - Wang, Cheng-Hsu; Lin, Cheng-Yao; Chen, Jen-Shi; Ho, Ching-Liang; Rau, Kun-Ming; Tsai, Jo-Ting; Chang, Cheng-Shyong; Yeh, Su-Peng; Cheng, Chieh-Fang; Lai, Yuen-Liang (Cancers, 2019)
Fatigue is a common and debilitating symptom in patients with advanced cancer, resulting in poor quality of life and reduced treatment efficacy. Phytotherapeutic agents have shown potential effects to relieve cancer-related fatigue in these patients. The aim of this study was to evaluate the efficacy and safety of Astragalus Polysaccharides injection and identify predictive factors associated with this treatment. Patients with advanced cancer receiving palliative care with moderate to severe cancer-related fatigue were enrolled in this study for two treatment cycles. Fatigue improvement response rates were analyzed as the primary endpoint at the end of the first cycle to determine treatment efficacy. The drug safety profile was evaluated by the reporting of adverse events. Three hundred and ten patients were enrolled in this study and 214 patients were included ITT population. Improvement in fatigue scores by at least 10% was observed in greater than 65% of subjects after one treatment cycle compared to scores at baseline. Patients with higher Karnofsky Performance Status (KPS) responded better to the Astragalus Polysaccharides injection. Drug-related adverse event rates were less than 9%. This study identified KPS as a promising predictive factor for the therapeutic efficacy of Astragalus Polysaccharides injection.